PENERAPAN STRATEGI PEMBELAJARAN INDUKTIF UNTUK MENINGKATKAN PEMAHAMAN KONSEPTUAL DAN PROSEDURAL MATEMATIKA SISWA MADRASAH ALIYAH - Ramlah . (Universitas Syiah Kuala, 2012)
Abstract Students' conceptual understanding of mathematics acquired through investment concepts and the association of a concept with other concepts. Procedural understanding is that task completion procedure can be given via a demonstration by the teacher. Assumed inductive learning strategies can improve conceptual understanding and procedural math students. This study was conducted to see the effect of inductive learning strategy to increase conceptual understanding and procedural mathematics student and it is a mixed method study. This study is a population that is all class XI IPA MAN Kuta Baro Aceh Besar, which consists of two classes. Obtain experimental class learning with inductive learning strategy and classroom learning gain control conventional. The research instrument consisted of conceptual understanding and procedural tests and interviews. Processing data by using SPSS, Microsoft Excel, t-test and Mann-Whitney test. Data processing results obtained: 1) there is no difference increased conceptual understanding of mathematics students who learn by inductive learning strategy and the learning with conventional learning, both in terms of overall student well in terms of student ratings of high, medium and low, 2) there is a difference increase in the procedural understanding of mathematical students are learning with inductive learning strategy and the learning with conventional learning, both in terms of overall students and students from low ratings, but there is no difference in terms of improvement when students rank high and medium. Results obtained some mistake interview students, among others: 1) erroneously determine the function of derivative with using the concept of limit because there was erroneous of multiplication algebra process, 2) erroneously write the example of function thas has derivative equals 3, that does not have derivative, and grouping function that has derivative 2 and it’snt 2 because they do not understand the concept of derivative, 3) erroneously indicate a function that has a derivative at a point because they don’t understand the mean of question (4) erroneously explain why the f '(0) is undefined for f(x) = because they don’t understand what is known on th question and divisibility by zero (5)erroneously conclude when a graph has a derivative around x=a because of they don’t understand the reason (6)erroneously determine the derivative quotient and the products of two functions because they don’t understand the definition of a derivative, the proces of algebra product, and it’s simplification (7) erroneously determine the derivative of the root form because there was an erroneous in the process of changing the root form. Keywords: Inductive Learning, Conceptual Understanding, Procedural Understanding